Pregnancies complicated with functioning adrenal adenomas causing severe obstetric outcomes: a 20-year experience at a tertiary center - Zhu, Caixia; Cai, Shiqin; Zhong, Xue; Huang, Linhuan (BMC endocrine disorders, 2024)
Functioning adrenal adenoma during pregnancy is rare, and the diagnosis is challenging owing to unspecific symptoms and restricted investigations. The obstetric outcomes of patients who undergo surgery during pregnancy or who receive only medical treatment are poorly described. The aim was to investigate the associations between functioning adrenal adenomas and obstetric outcomes. A retrospective study was performed in a tertiary center over 20 years. The clinical characteristics, management and obstetric outcomes of the diagnosed pregnant women were reviewed. A total of 12 women were diagnosed with functioning adrenal adenomas during pregnancy from January 2002 to September 2022. Eight women had cortisol-secreting adrenal adenomas, two had excessive catecholamine secretion, and two had primary aldosteronism. The initial symptoms of adrenal adenoma during pregnancy included hypertension or preeclampsia, gestational diabetes mellitus or prepregnancy diabetes mellitus, hypokalemia and ecchymosis. Four women underwent adrenalectomy during pregnancy, while 8 women received only medical therapy. Preterm birth occurred in all patients who received medicine, whereas 1 patient who underwent surgery experienced preterm birth. Among the 8 women in the medical treatment group, 3 had neonates who died. Once hypertension, hyperglycemia and hypokalemia occur during the 1st or 2nd trimester, pregnant women with adrenal adenomas should be evaluated via laboratory and imaging examinations. The maternal and fetal outcomes were unpredictable owing to the severity of adrenal adenoma, particularly in patients who received only medical treatment. Adrenalectomy should be recommended during pregnancy.